Detection and Quantification of Methyl tert-Butyl Ether-Degrading Strain PM1 by Real-Time TaqMan PCR - Hristova, Krassimira R. (American Society for Microbiology, 2001)
The fuel oxygenate methyl tert-butyl ether (MTBE), a widely distributed groundwater contaminant, shows potential for treatment by in situ bioremediation. The bacterial strain PM1 rapidly mineralizes and grows on MTBE in laboratory cultures and can degrade the contaminant when inoculated into groundwater or soil microcosms. We applied the TaqMan quantitative PCR method to detect and quantify strain PM1 in laboratory and field samples. Specific primers and probes were designed for the 16S ribosomal DNA region, and specificity of the primers was confirmed with DNA from 15 related bacterial strains. A linear relationship was measured between the threshold fluorescence (C(T)) value and the quantity of PM1 DNA or PM1 cell density. The detection limit for PM1 TaqMan assay was 2 PM1 cells/ml in pure culture or 180 PM1 cells/ml in a mixture of PM1 with Escherichia coli cells. We could measure PM1 densities in solution culture, groundwater, and sediment samples spiked with PM1 as well as in groundwater collected from an MTBE bioaugmentation field study. In a microcosm biodegradation study, increases in the population density of PM1 corresponded to the rate of removal of MTBE.